SAT0261 Which Conventional DMARD to Select in the Treatment of Psoriatic Arthritis (PSA)? Data From Nor-Dmard on 1351 Treatment Courses with Methotrexate (MTX), Sulfasalazine (SSZ) And Leflunomide (LEF). (23rd January 2014) - Lie, E.; Fagerli, K. M.; Rødevand, E.; Kalstad, S.; Mikkelsen, K.; Wierød, A.; van der Heijde, D.; Kvien, T. K.
Abstract : Background: MTX is probably the most commonly used DMARD to treat PsA wordwide and a recommended treatment for patients with active disease (1 ). In a recent publication of a negative placebo-controlled randomised trial of MTX in PsA, it was suggested that the sequencing of conventional DMARDs before biologics should be re-evaluated (2 ). Objectives: To assess the pattern for use of conventional DMARDs in PsA, and to compare the effectiveness of MTX, SSZ and LEF in a longitudinal observational study (LOS). Methods: Data were extracted from NOR-DMARD, a LOS of arthritis patients starting a new DMARD treatment, with follow-up at 3, 6, 12 months and then yearly. Patients diagnosed with PsA and starting treatment with MTX, SSZ or LEF were identified. We studied baseline characteristics and treatment responses (3 & 6 months) overall, and performed statistical comparisons between treatments including individual patients only. For the latter, the first inclusion per patient was selected. Unadjusted comparisons were done by ANOVA, Kruskall-Wallis or Chi 2 test, as appropriate, and analyses with adjustment for important baseline differences were performed by ANCOVA and logistic regression analysis. Results: A total of 1351 prescriptions of MTX (n=1000), SSZ (n=212) and LEF (n=139) in 1212 individual patients were identified – 128 patients were registered with ≥2 of the drugs and 11 patients with all 3 drugs. Among MTX/SSZ/LEF patients 71% vs. 61% vs. 6.5% were DMARD naïve, respectively, and 47% of patients on LEF had failed both MTX and SSZ. Patients treated with LEF also had longer disease duration. Mean baseline DAS28 for MTX/SSZ/LEF was 4.2/4.0/4.3, respectively. The baseline characteristics across groups for the first inclusion per patient (MTX n=949, SSZ n=177, LEF n=86) were very similar (baseline DAS28 4.2/3.9/4.3 for MTX/SSZ/LEF, respectively). Selected 6-month outcomes are shown in the table . Responses were numerically similar for the overall group of patients (n=1351). Comparison of 3-month responses yielded similar results. 2-year drug survival was superior for MTX (0.71) vs. SSZ (0.40; HR 1.96; p<0.001) and LEF (0.29; HR 2.47, p<0.001), with no significant difference between SSZ and LEF. Conclusions: MTX was the most commonly used first-line DMARD while LEF was rarely used as a first-line DMARD. Effectiveness was generally similar, but MTX performed better for some measures, including drug survival. References: Gossec L et al, Ann Rheum Dis 2012;71:4-12. Kingsley G et al, Rheumatology 2012;51:1368-77. Disclosure of Interest: None Declared